Hospital staff well‐being during the first wave of COVID‐19: Staff perspectives. (23rd October 2020) - Digby, Robin; Winton‐Brown, Toby; Finlayson, Felicity; Dobson, Hannah; Bucknall, Tracey
Abstract: The purpose of this research is to determine the impact of working during the early stage of the COVID‐19 pandemic on the well‐being of staff at one 600‐bed acute hospital in metropolitan Melbourne, Australia. This exploratory study is part of a larger mixed methods survey project, reporting the qualitative data from an on‐line survey of clinical staff working at one acute hospital between April 16th and May 13th, 2020 during the COVID‐19 pandemic. Responses to five free‐text questions were analysed using inductive content analysis. 321 medical, nursing, allied health and non‐clinical staff responded to the survey. Respondents reported anxiety, fear and uncertainty related to the pandemic, from the perspectives of work, home, family and community. They reported feeling confused by inconsistent messages received from government, hospital executive, managers and media. Seven themes were identified: (i) worrying about patient care, (ii) changed working conditions, (iii) working in the changed hospital environment, (iv) impact of the pandemic, (v) personal isolation and uncertainty, (vi) leadership and management and (vii) additional support needed for staff. Despite the pandemic being comparatively well‐controlled in Australia, all disciplines reported a high degree of anticipatory anxiety. Staff working in healthcare require both managerial and psychological support to minimise anxiety and promote well‐being and resilience in order to deal with the health crisis. Regular unambiguous communication directing the way forward is crucial.